The kinetics and mechanism of tin(II) octoate-initiated polymerization of epsilon-caprolactone - Duda, A.; Kowalski, A.; Libiszowski, J. (Polimery, 2022)
A review with 34 references covering recent studies on tin(II) octoate (Sn(Okt)2)-initiated polymerization of ε-caprolactone in tetrahydrofuran as solvent at 80oC is presented. Kinetic data (by dilatometry) and structural studies (by MALDI-ToF mass spectrometry) have shown the Sn(Okt)2-initiated polymerization to proceed by the active-chain-end mechanism (eqns. 2a—2d) with tin(II) alkoxides as active centers. The actual initiator is OktSnOR which is formed in the reaction of exchange -SnOkt + ROH U -Sn-OR + OktH, where ROH is the compound containing the hydroxyl group like water, alcohol or a hydroxyacid, present accidentally in, or added intentionally to, the polymerization mixture. These results rule out the activated-monomer mechanism (eqns. 1a—1b) as a possibility, according to which propagation would involve a nucleophilic attack of the -OH group-terminated macromolecule on the monomer -Sn(Okt)2 complex.